Unequal Reward for Equal Work? Understanding Women's Work and Wage Discrimination in India Through the Meniscus of Social Hierarchy. Issue 1 (May 2020) - Singh, Pushpendra; Pattanaik, Falguni
The Indian society is one of the most unequal societies of the world and divided into different social hierarchies of caste, class, religion, etc. Caste is a determinant of power, economic inequality, poverty and discrimination in contemporary India. When it comes to women, they face the dual burden of discrimination, first gender based and, second, caste based. The practice of discrimination persists between Dalit/tribal and upper-class women, but still, Dalit women are trying to come out of this unequal treatment. Hence, this study investigates the magnitude of discrimination among women workers in terms of the social hierarchy and relative factors responsible for workforce discrimination. Furthermore, this study examines the extent of wage differential between Dalit/tribal and upper-class women workers. The study has used the data of the 50th Employment and Unemployment Survey to the Periodic Labour Force Survey (PLFS) from 1993–1994 to 2017–2018 by the National Sample Survey Office (NSSO). In the first part of the analysis, this study explains how and why the women workforce is decreasing, particularly as far as Dalit/tribal women are concerned. Subsequently, the relative contributions of socio-economic conditions in the women workforce have been assessed using logistic regression. However, the second part of the study examines the wage differential between general and Dalit/tribal women and the extent of wage discrimination using the Oaxaca–Blinder decomposition method. The study reveals that the women workforce has been consistently declining and the vulnerability is intense among Dalit/tribal women. Furthermore, it has been observed that the social hierarchy (caste) is a decisive factor for the remuneration (wage) in the labour market and over the period of study, the wage discrimination between Dalit and upper-caste women has significantly increased.